2015
DOI: 10.1186/s12943-015-0337-x
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-31 controls G protein alpha-13 (GNA13) expression and cell invasion in breast cancer cells

Abstract: BackgroundGα13 (GNA13) is the α subunit of a heterotrimeric G protein that mediates signaling through specific G protein-coupled receptors (GPCRs). Our recent study showed that control of GNA13 expression by specific microRNAs (miRNAs or miRs) is important for prostate cancer cell invasion. However, little is known about the control of GNA13 expression in breast cancers. This project was carried out to determine (i) whether enhanced GNA13 expression is important for breast cancer cell invasion, and (ii) if so,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 48 publications
1
56
0
1
Order By: Relevance
“…Overexpression of miR-10b in breast cancer cells can inhibit the expression 25 Huang et al, 32 Bahena-Ocampo et al, 33 Liang et al, 34 Ma et al, 35 Petrovic, 36 Yan et al 37 51 Rasheed et al, 52 Tavazoie et al, 53 Chou et al, 54 Zhang et al 55 43 A study showed that the upregulation of miR-155 can facilitate tumor angiogenesis, while it is associated with a poor prognosis for triple-negative breast cancer patients. 44 Kong et al 45 reported that miR-155 can act on TGF-β/Smad4 signaling through RhoA, thereby promoting the EMT; in contrast, knockdown of miR-155 can significantly inhibit the TGF-β/Smad4-induced EMT.…”
Section: Mirnas Promoting Breast Cancer Invasion and Metastasismentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of miR-10b in breast cancer cells can inhibit the expression 25 Huang et al, 32 Bahena-Ocampo et al, 33 Liang et al, 34 Ma et al, 35 Petrovic, 36 Yan et al 37 51 Rasheed et al, 52 Tavazoie et al, 53 Chou et al, 54 Zhang et al 55 43 A study showed that the upregulation of miR-155 can facilitate tumor angiogenesis, while it is associated with a poor prognosis for triple-negative breast cancer patients. 44 Kong et al 45 reported that miR-155 can act on TGF-β/Smad4 signaling through RhoA, thereby promoting the EMT; in contrast, knockdown of miR-155 can significantly inhibit the TGF-β/Smad4-induced EMT.…”
Section: Mirnas Promoting Breast Cancer Invasion and Metastasismentioning
confidence: 99%
“…In vitro experiments showed that miR-31 can inhibit the invasion and metastasis of breast cancer cells. 52 Moreover, miR-126, miR-206, and miR-335 can suppress breast cancer metastasis. 53 Chou et al 54 demonstrated that the transcription factor GATA3 can suppress breast cancer metastasis by upregulating miR-29b expression.…”
Section: Mirnas Inhibiting Breast Cancer Invasion and Metastasismentioning
confidence: 99%
“…There is strong evidence that GNA13 (α subunit of a heterotrimeric G protein) expression is involved in breast tumorigenesis through enhancement of cell invasion, while partially regulated post-transcriptionally by miRNA-31 in breast cancer cell lines. Down-expression of miRNA-31 and hence increased GNA13 level leads to cancer progression (10). Based on previous findings provided by several studies miRNA-31 seems to be considered especially as a major regulator of metastasis formation in breast cancer patients as well as a crucial suppressor of mammary stem cells (MSC) neoplastic transformation.…”
mentioning
confidence: 99%
“…These GPCRs can signal through heterotrimeric G proteins, especially the GNA12/GNA13 subfamily which has been shown to mediate cancer cell invasion and metastasis2223242526. It was reported that GAN13 had been closely associated with tumor progression in different types of human cancers, such as prostate, breast, colorectal, pancreatic and gastric cancers1617192027. These findings reveal a potential carcinogenic role of GNA13 in multiple human malignancies.…”
Section: Discussionmentioning
confidence: 87%
“…Recently, increased expression of GNA13 has been found in several types of malignancies, especially in more aggressive breast and prostate cancer. Furthermore, the impact of this upregulation could contribute to cancer cell invasion and migration1617. Li and the colleagues found GNA13 played a critical role in lysophosphatidic acid (LPA)-stimulated invasive migration of pancreatic cancer cells18.…”
mentioning
confidence: 99%